Um sistema integrado de modelagem de cultivos e doenças: brusone no trigo - Bavaresco, Jorge Luis Boeira (2015)
The blast is a disease that causes considerable losses in wheat and slows down the advance of this crop in Brazil. As wheat has a signi cant economic importance, predicting blast epidemics on wheat or providing information to assist the understanding of this disease, it is useful for the eld of agronomy. Thus, the aim of this study is to develop a tool to assist decision making for the management of the risk of wheat blast, facilitating the implementation and visualization of disease simulation models and pests in crops, leaving aside the great complexity involved in such processes and providing useful information. The research has as speci c objectives the developing of a web tool to use models of simulation and assessment of the risk of blast epidemics in Brazil and the United States. It was obtained results in a tool that allows the use of simulation of the growth and development of the crops web designs easily and quickly. Another result was that the tool made it possible to perform experiments planned for the state of Paraná locations in Brazil, in the years 2001-2012 and for the state of Kentucky in the United States in the years 2009-2014, providing information on outbreaks of disease in these two countries. Thus, the simulation model of the wheat blast, along with the web tool for running simulations of the growth and development of crops that have been developed in this research become relevant to the areas of computing, simulation and agronomy.